A modified Ricatti approach to partially solvable quantum Hamiltonians. I: Finite Laurent type potentials - Salem, L. D.; Montemayor, Rafael (Comisión Nacional de Energía Atómica; Argentina)
Fil: Salem, L. D. Comisión Nacional de Energía Atómica; Argentina